The Relationship Between Iranian EFL Learners’ Personality Traits and Their Mobile Assisted Vocabulary Learning - Elham Mohammadi; Robab Khosravi; Azam Masoumi (Journal of Language Horizons, 2022)
The growing inclusion of technological devices in language learning calls for exploring their efficacy and determining to what extent learners’ characteristics mediate their effectiveness. In light of these concerns, the current study has sought to examine the relationship between learning English vocabulary via mobile phone and the learners’ personality traits. The participants of the study were 100 intermediate English as foreign language (EFL) learners studying English at the University of Zanjan, Zanjan, Iran. Sixty American English idioms were chosen and made available in a Telegram channel, during a six-week period of treatment to provide the participants with Mobile-Assisted Language Learning (MALL). A researcher-designed achievement test was administered to assess the learners’ vocabulary learning via mobile phone. Big Five Inventory (BFI)” (John et al. 2008) was used to estimate the learners’ personality traits. The data analyses showed no significant correlation between the variables; however, simultaneous multiple regression offered extraversion as the unique significant predictor. The results revealed MALL not only frees the learners from the restrictions of time and place, but also minimizes the possible intervention of learners’ characteristics in the process of language learning. The fruitfulness of MALL in leaving behind students’ characteristics has important implications for both educators and practitioners.